Speech Variation, Utility, and Game Theory. Issue 11 (November 2013) - Dror, Moshe; Granot, Daniel; Yaeger‐Dror, Malcah
Abstract We review a new perspective for analyzing linguistic variation, diffusion, and change, by introducing into this 'arena' the economists' perception of strategic individual interactions. We invoke basic game theory principles to explain linguistic outcomes of individual speech production in a variety of interactional social settings. We present real‐life examples that illustrate our game perspective regarding linguistic interactions and present a number of mappings into well‐known game constructs such as the Prisoners' Dilemma, iterated dominance, and extensive form games. Our purpose is to suggest a game theory 'prism' as a plausible methodology for analysis of individual interactional linguistic situations.